2010
DOI: 10.1007/s10682-010-9401-6
|View full text |Cite
|
Sign up to set email alerts
|

To compete or not to compete: an experimental study of interactions between plant species with contrasting root behaviour

Abstract: Game-theoretic models predict that plants with root systems that avoid belowground competition will be displaced by plants that overproduce roots in substrate shared with competitors. Despite this, both types of root response to neighbours have been documented. We used two co-occurring clonal species (Glechoma hederacea and Fragaria vesca) with contrasting root responses to neighbours (avoidance of competition and contesting of resources, respectively) to examine whether functional variation in other traits af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…The direction and magnitude of these plastic responses was not significantly correlated with competitive ability. These results support findings showing that plant species exhibit a wide range of behavioural strategies to deal with belowground competition (Semchenko et al 2007(Semchenko et al , 2010Valverde-Barrantes et al 2013;Belter and Cahill 2015). Therefore, although plasticity in functional traits in response to competition may play an important role in community assembly, the apparent diversity of possible responses makes it difficult to predict the way in which it operates.…”
Section: Discussionsupporting
confidence: 82%
“…The direction and magnitude of these plastic responses was not significantly correlated with competitive ability. These results support findings showing that plant species exhibit a wide range of behavioural strategies to deal with belowground competition (Semchenko et al 2007(Semchenko et al , 2010Valverde-Barrantes et al 2013;Belter and Cahill 2015). Therefore, although plasticity in functional traits in response to competition may play an important role in community assembly, the apparent diversity of possible responses makes it difficult to predict the way in which it operates.…”
Section: Discussionsupporting
confidence: 82%
“…These species exhibit avoidance of root competition and are not competitively inferior to the species that does not (e.g. Potentilla reptans, Ranunculus repens, genus Fragaria) (Steinbach & Gottsberger 1994;Leeflang 1999;Vermeulen et al 2008;Semchenko et al 2010). It was found that G. hederacea invests preferentially in rapid exploitation of unoccupied places, whereas F. vesca invests in increasing the competitive ability and local persistence of established ramets (Semchenko et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Potentilla reptans, Ranunculus repens, genus Fragaria) (Steinbach & Gottsberger 1994;Leeflang 1999;Vermeulen et al 2008;Semchenko et al 2010). It was found that G. hederacea invests preferentially in rapid exploitation of unoccupied places, whereas F. vesca invests in increasing the competitive ability and local persistence of established ramets (Semchenko et al 2010). Slender speedwell grew very fast from two-node segments in bare loam soil (Harris & Lovell 1980), but its body is delicate and not so competitive with other species in the lawn.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratory or greenhouse experimental studies tested these interactions by examining root-placement patterns (Huber-Sannwald et al 1998, Falik et al 2003, Holzapfel and Alpert 2003, Gruntman and Novoplansky 2004, Semchenko et al 2007, Semchenko et al 2010. In general, clonal plants appear to be capable of discriminating between the roots of clonemates and those of other genets and can respond by changing root-placement patterns (de Kroon 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies have tested biotic interactions between clonal plant species. Semchenko and her colleagues (Semchenko et al 2007, Semchenko et al 2010 examined biotic interactions between woodland strawberry (Fragaria vesca) and ground ivy. Root behavior in response to interspecific competition varied between the species.…”
Section: Introductionmentioning
confidence: 99%